Analisa Laju Korosi Galvalum I dan Galvalum II Terhadap Media Air Sumur dan Air Laut - Masrufaiyah; Agus Setiyo Umartono; Nando Arifal Hisyamuddin (Wahana Teknik, 2020)
The use of lightweight steel roof trusses (galvalume) is currently increasing, given the increasingly expensive and scarce wood prices. When compared to wood, galvalume is also more durable because it cannot be eaten by termites. In this study, the quality of 2 galvalumes, namely aplus and galvatruss, will be tested against the corrosion rate due to rainwater and seawater. The purpose of this study was to determine the effect of differences in the quality of galvalume on the corrosion rate due to rainwater and seawater. This corrosion rate study was carried out directly electrochemically using a tool to measure the corrosion rate, namely potentiostat, using regression methods and polarization techniques, namely based on electrochemical reactions at the anode and cathode that occurred in the galvalume constituent material which had been electrified. The results of the study concluded that galvatruss galvalume is better than aplus galvalume. This is evident in the corrosion rate test, the value of the corrosion rate of galvatruss galvalume is lower than the value of the aplus galvalume corrosion rate, both with rainwater and seawater. Keywords: corrosion, galvalume, rates, seawater, wellwater.